(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
According to three years of research, the influence of mineral fertilizers and growth regulators under different sowing methods on the dry matter formation of spring camelina varieties has been established. Formulation of the problem. The productivity indicators of spring ryegrass plants - the dynamics of dry matter growth are important for the formation of a large seed yield and characterize the efficiency of the assimilation surface of plants. Therefore, studies on the dynamics of dry matter accumulation on the productivity of spring ryegrass are relevant and are related to the improvement of its cultivation technology. Purpose. Establishing the features of the formation of dry matter of spring ryegrass under the influence of mineral fertilizers, plant growth regulators and sowing methods in the conditions of the Southern Steppe of Ukraine. Methods. The study was conducted in 2023–2025 at the experimental field of the Institute of Oilseed Crops in the Zaporizhzhia district of Zaporizhzhia region. To address the research objectives, a four-factor field experiment was carried out. Factor A – row spacing (2 variants). Factor B – application of mineral fertilizers (4 variants). Factor C – variety (2 variants). Factor D – application of growth regulators (4 variants). The total number of experimental variants was 64. Replication was threefold. The establishment of the experiment, accounting, measurements, and accompanying observations were conducted according to standard field experiment methodologies. Results. The greatest increase in dry matter of one plant, depending on the background of mineral fertilizers and the use of growth regulators, was obtained in the interphase period of flowering-ripening: with a row spacing of 15 cm, 0.90–1.29 g/plant for the Prestige variety and 0.83–1.29 g/plant for the Slavutych variety; with a row spacing of 70 cm, 1.07–1.64 g/plant for the Prestige variety and 1.05–1.55 g/plant for the Slavutych variety. The greatest values ​​of dry matter increase of one plant of red spring wheat were obtained with a row spacing of 70 cm, with the application of mineral fertilizers at a dose of N40P40K40. The use of growth regulators contributed to an increase in dry matter increase rates for all interphase periods, sowing methods and mineral nutrition backgrounds. The maximum values ​​of dry matter increment of spring ryegrass per hectare for both sowing methods for both the Prestige and Slavutych varieties were provided by growing with a row spacing of 15 cm and applying mineral fertilizers at a dose of N40P40K40. The greatest dry matter increment in the interphase flowering-ripening period – 4.72 t for the Prestige and Slavutych varieties was obtained when sowing with a row spacing of 15 cm against the background of applying mineral fertilizers at a dose of N40P40K40 with spraying of crops with the growth regulator Rost-concentrate in the rosette phase. Conclusions. The highest mass of dry matter of 6.99 t/ha for the Prestige variety and 7.09 t/ha for the Slavutych variety, including the vegetative part of 5.67 t/ha (81.2%) and 5.69 t/ha (80.4%) and seeds of 1.32 t/ha (18.8%) and 1.40 t/ha (19.6%), respectively, was obtained when growing with a row spacing of 15 cm against the background of the application of mineral fertilizers N40P40K40 with spraying of crops in the rosette phase with the growth regulator Rost-concentrate.